Pengaruh Rendaman Terhadap Perubahan Sifat Mekanik Komposit Polyester Resin - Partikel Arang Sekam Padi - Siswanto; Fahmi Eka Saputra; Basmal (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) Politeknik Pratama Mulia Surakarta, 2016)
Engineering materials utilizing waste Charcoal Husk Rice Particles (PASP) as a filler in the unsaturated polyester resin matrix composite BQTN 157, aims to determine the effect of soaking to changes in mechanical properties of flexural strength and impact strength in the composite specimen. Polyester resin material mixed with a kind of BQTN 157 charcoal husk rice particles (PASP) vf 40%, 1% wt hardener. Material is poured into the mold, holding time 30 minutes. Composites are made based on the test specimen flexural and impact test specimens. Composite given treatment soaking for 150 hours with a variation of the fluid; rain water, mineral water, and water wells with 10 wt% water vinegar. Specimens in doing testing of flexural strength ASTM D 790 standards and impact testing standard ASTM D 5941 to determine the mechanical properties of the composite. Testing Results indicates that the flexural strength of the composite without treatment 35,50 N / mm2, while the composite with the treatment had an average flexural strength: mineral water Soaking 34.53 N / mm2, rain water soaking 34.66 N / mm2, soaking water wells + 10% Vinegar 32.89 N / mm2,. Tests on the impact strength shows that the impact strength of the untreated composites 4,16 kJ / mm2, while composites with bath treatment had an average impact strength as follows: Soaking mineral water 3,62 kJ / mm2, rain water soaking 3,35 kJ / mm2 , well water soaking + 10% Vinegar 2,98 kJ / mm2.